Growth and optical properties of CaxCoO2 thin films. (15th November 2021) - Xin, Binbin; Le Febvrier, Arnaud; Wang, Lei; Solin, Niclas; Paul, Biplab; Eklund, Per
Graphical abstract: Highlights: Phase-pure Cax CoO2 thin films were obtained by annealing Ca(OH)2 /Co3 O4 multilayers. The Cax CoO2 thin films showed good transmittance properties. The electrical conductivity of Cax CoO2 was improved by incorporating Ca3 Co4 O9 . Abstract: The layered cobaltates A x CoO2 (A = Li, Na, Ca, Ba, Sr) are of interest for energy applications such as thermoelectrics and batteries. However, it is challenging to obtain these phases in pure from as thin films. Here, phase-pure Cax CoO2 (x ~ 0.5) thin films were obtained by annealing of Ca(OH)2 /Co3 O4 multilayers made by moisture treatment of sputter-deposited CaO/Co3 O4 multilayer films. The pure Cax CoO2 thin films exhibit an average optical transmittance of approximately 36% in the visible region and greater than 70% in the near-infrared (NIR) region. In addition, the electrical conductivity can be increased by incorporating a secondary Ca3 Co4 O9 phase into the Cax CoO2 thin film without large changes in optical properties and Seebeck coefficient.